Microwave synthesis of zinc oxide/reduced graphene oxide hybrid for adsorption-photocatalysis application - Omar, Fatin Saiha; Huang, Nay Ming; Syed Muhamad Hafiz,; Lim, Hong Ngee (Hindawi Publishing Corporation, 2014)
This work reports on synthesis of zinc oxide/reduced graphene oxide (ZnO/rGO) nanocomposites in the presence of diethylenetriamine (DETA) via a facile microwave method. The X-ray diffraction (XRD) patterns of the nanocomposites correspond to the ZnO hexagonal phase wurtzite structure. The high-resolution transmission electron microscopy (HRTEM) images revealed that the ZnO nanorods, with an average length : diameter ratio of 10, were successfully deposited on the rGO sheets. Under the irradiation of sunlight, the nanocomposites showed enhanced adsorption-photocatalysis by more than twofold and photocurrent response by sixfold compared to the ZnO. The excellent photoactivity performance of the nanocomposites is contributed by smaller ZnO nanorod and the presence of rGO that acts as a photosensitizer by transferring electrons to the conduction band of ZnO within the nanocomposite during sunlight illumination.